2003
DOI: 10.1074/jbc.m304112200
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated Protein Kinase Regulates HNF4α Transcriptional Activity by Inhibiting Dimer Formation and Decreasing Protein Stability

Abstract: AMP-activated protein kinase (AMPK) is the central component of a cellular signaling system that regulates multiple metabolic enzymes and pathways in response to reduced intracellular energy levels. The transcription factor hepatic nuclear factor 4␣ (HNF4␣) is an orphan nuclear receptor that regulates the expression of genes involved in energy metabolism in the liver, intestine, and endocrine pancreas. Inheritance of a single null allele of HNF4␣ causes diabetes in humans. Here we demonstrate that AMPK directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
144
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(161 citation statements)
references
References 54 publications
(54 reference statements)
12
144
2
3
Order By: Relevance
“…Moreover, HDAC2 overexpression induced greater phosphorylation of HNF-4A at the Ser304 epitope ( Figure 4F), which is phosphorylated by AMPK to inhibit its transcriptional activity. 20 Similar results were obtained from the hippocampus of 12-month-old 3xTg-AD mice www.moleculartherapy.org ( Figures 4G-4I). Therefore, the suppression of miR-101b by HDAC2 was further increased by activation of AMPK, which forms a strong regulatory feedback loop.…”
Section: Hdac2 Negatively Regulates the Binding Of Hnf-4a To The Mir1supporting
confidence: 79%
“…Moreover, HDAC2 overexpression induced greater phosphorylation of HNF-4A at the Ser304 epitope ( Figure 4F), which is phosphorylated by AMPK to inhibit its transcriptional activity. 20 Similar results were obtained from the hippocampus of 12-month-old 3xTg-AD mice www.moleculartherapy.org ( Figures 4G-4I). Therefore, the suppression of miR-101b by HDAC2 was further increased by activation of AMPK, which forms a strong regulatory feedback loop.…”
Section: Hdac2 Negatively Regulates the Binding Of Hnf-4a To The Mir1supporting
confidence: 79%
“…However, we cannot exclude the possibility that the receptor localized to the plasma membrane senses luteolin and that the addition of glucoside makes it inaccessible to the receptor. It has been reported that luteolin enhances the phosphorylation of AMP-activated protein kinase in HepG2 cells (38), and AMP-activated protein kinase directly phosphorylates HNF4␣ and represses its transcriptional activity (39). Thus, it is conceivable that luteolin indirectly suppressed HNF4␣ activity through the stimulation of AMP-activated protein kinase signaling in addition to direct binding to its LBD as an antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK phosphorylation of ChREBP inhibits ChREBP translocation to the nucleus. AMPK phosphorylation of HNF-4␣ impairs HNF-4␣ dimer stability and DNA binding (42). Two groups have reported that fatty acids activate AMPK through phosphorylation of AMPK (24,43).…”
Section: Mechanisms Controlling L-pk Promoter Activitymentioning
confidence: 99%